Physicochemical, microbiological characterization and proteolysis of Algerian traditional Bouhezza cheese prepared from goat's raw milk. (12th April 2020) - Medjoudj, Hacène; Aouar, Lamia; Derouiche, Meriem; Choiset, Yvan; Haertlé, Thomas; Chobert, Jean-Marc; Zidoune, Mohammed Nasreddine; Hayaloglu, Ali Adnan
Abstract: Bouhezza is an Algerian traditional cheese made using different types of milk (goat, sheep and cow), ripened in a goat-skin or sheep-skin bag called Chekoua or Djeld of Bouhezza . The objective of the study was the characterization of Bouhezza cheese through ten cheese preparation trials using goat raw milk. The chemical and microbiological composition and proteolysis were monitored on ripened samples. The physicochemical characteristics showed that Bouhezza is acidic with a pH value of 3.95 and 2.36% for titratable acidity as lactic acid, 13.20% for protein and 12.74% for fat. At the end of ripening, Bouhezza was classified to be a ripened, soft and mid-fat cheese. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) of Bouhezza samples showed low proteolysis after 30 days of ripening. Microbiological results showed a high content of lactic acid bacteria (LAB), 8 to 9 log cfu/ g, an absence of pathogenic bacteria, and a low level of contamination flora. This makes the cheese a healthy product and of an acceptable hygienic quality. Four proteolytic lactic acid bacteria were identified by 16S ribosomal deoxyribonucleic acid (rDNA) sequencing: two strains of Enterococcus faecalis, one E. faecium, and one Lactobacillus paracasei ssp . paracasei . Reversed phase-high performance liquid chromatography (RP–HPLC) of the soluble fraction at pH 4.4 showed changes occurred during ripening. This work highlights, characterizes, and improves the knowledge of cheese Bouhezza made with raw goat's milk. This product is rich in nutrients, such as proteins and minerals, that are useful to the consumer.